Targeting the Tumor Microenvironment to Enhance Pediatric Brain Cancer Treatment. Issue 4 (July 2015) - Batista, Ana; Riedemann, Lars; Vardam, Trupti; Jain, Rakesh K.
<x xml:space="preserve">Abstract</x> Abstract Strategies targeting the microenvironment of pediatric brain cancers have the potential to improve the efficacy of standard and genome-based molecular therapeutics. These strategies also have the potential of helping resolve many of the challenges associated with developing new drugs and running clinical trials for relatively small pediatric brain tumor population. Disrupting vital paracrine and physical interactions between cancer cells and surrounding stroma, targeting and normalizing the abnormal tumor vasculature, and/or inducing antitumor immunity represent some of the most promising approaches. A comprehensive characterization of the pediatric brain tumor microenvironment's composition and function and its modulation by chemoradiation and molecularly targeted therapies is warranted to develop and effectively implement these approaches.